The mechanism of nano-network structure formed by friction-induced pozzolanic silicate. (April 2023) - Zheng, KaiLong; Xing, Hui; Zhang, Lanting; Yan, PengFei; Wei, XianShun; Yan, Biao
Abstract: Friction transfer film is one of the influencing factors in the evolution of the subsurface microstructure of frictional contact materials. An iron-poor friction transfer film of aluminum-based composites with silicon carbide and pozzolanic silicate particles as the reinforcing phase was investigated utilizing scanning electron microscope, focused ion beams, transmission electron microscopy and energy dispersive X-ray analysis. The results showed that the friction transfer film contained ultra-fine aluminum, nano-aluminum, broken silicon carbide and silicate particles, as well as in-situ generated andradite and gismondine, which self-assemble into a nano-network structure to support the formation of the friction transfer film. Thermodynamic calculations and high-resolution transmission electron microscopy clarified the formation mechanism of andradite and gismondine. Highlights: Pozzolanic silicate retains nano-aluminum, ultra-fine-grained aluminum, and silicon carbide in the friction transfer film. Pozzolanic silicate generates pozzolanic reaction products during friction, which are andradite and gismondine. The formation of andradite is associated with the counter-body, and that of gismondine is related to andradite.